THE EFL LEARNERS’ PERCEPTIONS AND REALIZATIONS OF FORMULAIC SEQUENCES IN CASUAL CONVERSATION - Khusnita, Dafi; Rukmini, Dwi (English Education Journal, 2016)
This research is descriptive qualitative study aiming at finding out EFL learners’ perceptions and realizations of formulaic sequences in casual conversations and seeing how the perceptions relate to the realizations. 13 students of English Department of Unnes Graduate Program were chosen as the participants of the study. Two sources of data were used in this study: interview and audio recordings of the casual conversations. The result of the interview revealed that the learners generally have positive perceptions of formulaic sequences. However, they do not ever get any materials about formulaic sequence in their EFL learning so that they do not really familiar with its concept.From the analysis of the learners’ casual conversations using the combination of Biber et al. (1999) and Celce-Murcia (2007) categorization system of formulaic sequences, all six types of formulaic sequences are found: inserts, collocation, routines, multi-word units, binomial expressions, and idioms. Furthermore, it is found that learners’ problem in realizing formulaic sequences includes the tendency to simply use the expressions they heard from any sources without considering the appropriateness of the expressions, the difficulty in using correct formulaic sequences to be used in the given situation, theidiomaticity of formulaic sequences, the tendency to translate Indonesian expressions into English literally word by word, and problems related to grammar. The learners’ perceptions of formulaic sequences are related to its realizations in terms of the problems they faced in using formulaic sequences in casual conversation.